Population size and breeding success of the Icelandic Whooper Swan Cygnus cygnus: results of the 2015 international census - Hall, Colette; Crowe, Olivia; McElwaine, Graham; Einarsson, Ólafur; Calbrade, Neil; Rees, Eileen C. (Wildfowl, 2016)
The seventh international census of Whooper Swans in Britain, Ireland, Iceland and the Isle of Man took place in January 2015, to update estimates of the size and midwinter distribution of the Icelandic Whooper Swan population. The 34,004 swans recorded represented a 16% increase in numbers compared to the previous census in 2010, a 155% increase on counts made in 1995, and was the highest census total to date. The drivers behind this increase have yet to be determined, but it seems that it is not solely attributable to an improvement in breeding success in recent years and that changes in survival rates and perhaps interchange with the Northwest Mainland Europe population may also be accountable for the trend. Overall, 35.5% of the population (12,083 birds) was recorded in England, 34.9% (11,852) in the Republic of Ireland, 11.1% (3,784) in Scotland, 10.4% (3,518) in Northern Ireland, 7.4% (2,520) in Iceland and < 1% (247) in Wales and the Isle of Man. There was a significant decline in the proportion of birds wintering in Northern Ireland and the Republic of Ireland in comparison with the 2010 census, whilst conversely England saw a notable increase. Although a higher proportion of the population was recorded in Scotland in 2015 than in 2010, the results indicate a continuation of the overall shift to the southeast in the swans’ winter distribution, recorded since the first international census in 1986. As in previous censuses, the majority of birds in Britain and Ireland were on pasture and arable land, whereas in Iceland the birds were foundmainly on riverine and coastal habitats.